2023
DOI: 10.1101/2023.09.06.556618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topographic Axes of Wiring Space Converge to Genetic Topography in Shaping Human Cortical Layout

Deying Li,
Yufan Wang,
Liang Ma
et al.

Abstract: Genetic factors have involved the gradual emergence of cortical areas since the neural tube begins to form, shaping the specialization of neural circuits in the human brain. Informed by invasive tract-tracing measurements, the cortex exhibits marked interareal variation in connectivity profiles, yet how this spatial variation is encoded in genetics remains unclear. Instead of considering a complex one-to-one mapping between genetic coding and interareal connectivity variation, we hypothesized the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 167 publications
(326 reference statements)
0
0
0
Order By: Relevance
“…The connectivity divergence and its underlying genetic associations were further investigated. The filtered genes identified by PLSR using the AHBA dataset are implicated in synapse and axon-related processes and neuronal projections, which are at the basis of macroscale anatomical connections 25,100 . Several genes, including EFCAB1 , C2CD4C, and SYT17 , were predicted to enable calcium ion binding 101,102 , which plays an important role in signal transduction and other cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connectivity divergence and its underlying genetic associations were further investigated. The filtered genes identified by PLSR using the AHBA dataset are implicated in synapse and axon-related processes and neuronal projections, which are at the basis of macroscale anatomical connections 25,100 . Several genes, including EFCAB1 , C2CD4C, and SYT17 , were predicted to enable calcium ion binding 101,102 , which plays an important role in signal transduction and other cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have mapped chimpanzee brain connections using diffusion MRI and revealed substantial interspecies differences with humans 14,16,17,[20][21][22][23] . Moreover, understanding brain evolution requires a genetic perspective, as genetic factors strongly influence neural connectivity and uncover molecular mechanisms driving interspecies differences in brain connections, revealing insights into cognitive diversity and adaptation among primates 24,25 . However, comprehensive whole-brain connectional analyses and comparisons between chimpanzees and humans, coupled with genetic investigations into species differences in brain connections, are still lacking.…”
Section: Introductionmentioning
confidence: 99%